The Effect of the Application of the Game Method on Locomotor Basic Movement Material on Learning Outcomes of Grade 2 Students at State Elementary School 143 Seluma - Wibowo, Ananda; Sumantri, Ajis; Perdima, Feby Elra (UNIVED Press, Universitas Dehasen Bengkulu, 2025)
This study aims to determine the effect of student learning outcomes in using game methods in class 2 learning material on locomotor basic movements at SD Negeri 143 Seluma. The type of research used in this research is quantitative with experimental methods. The type of experimental research used in this research is Pre-Experimental Design with One-Group Pretest- Posttest type. This research was conducted at SD Negeri 143 Seluma in class 2 of the 2024/2025 academic year. The time used for data collection was from September 2024 to March 2025. The research population was taken from students of SD Negeri 143 Seluma, with a sample size of 13 students. Furthermore, the data analysis techniques used in this study are descriptive data analysis and quantitative data analysis. In quantitative data analysis, researchers used normality test (Saphiro Wilk) and hypothesis testing (paired sample t-test). All calculations used in this study used SPPS version 21. The results of this study obtained pretest scores with an average score of 6.62. Then obtained an average posttest of 9.31. From the results of the T-test conducted, significant results were obtained. This is evidenced by the Sig. (2- tailed) of 0.000, where the Sig. value is <0.05 then Ha is accepted and Ho is rejected. So it can be concluded that the game method affects the learning outcomes of grade 2 students at SD Negeri 143 Seluma. This can be interpreted that the game method can be used as a reference for teachers to improve student learning outcomes.